DARI SUBSISTENSI KE KONTRIBUSI: ANALISIS MOBILITAS VERTIKAL ANTARGENERASI PADA ALUMNI BEASISWA DANA DESA DI DAERAH 3T - Tirtania Sasea; Kabul Putra Imanuel Mone; Mises Boisana Carles Abineno (STKIP Pesisir Selatan, 2026)
Education improves the quality of human resources, driving sustainable economic prosperity. Producing quality human resources can be achieved through education at a specific level or through training aimed at developing talents. Education is an essential and inseparable component of life. For children in the 3T (third-most remote) regions, the desire to pursue higher education is a strategic effort to improve their standard of living. However, rising tuition costs and unstable family incomes hinder village children's pursuit of further education. This research employed a qualitative case study approach. This method was chosen to specifically and in-depth understand the economic transformation of village fund scholarship recipient families after they graduated from college. The results show that scholarship recipients successfully transformed their mentality, family status, and economic growth. The most fundamental change in assistance was the shift in mindset from dependent families to independent families. Improvements were seen in the job profiles of both the parent generation and the university alumni who received the scholarships.